Persistent PR segment change in malignant pericardial disease. Issue 1 (December 2016) - Ahluwalia, M.; O'Quinn, R.; Ky, B.; Callans, D.; Kucharczuk, J.; Carver, J.
Abstract Background Electrocardiographic changes may manifest in patients with pericardial effusions. PR segment changes are frequently overlooked, but when present, can provide diagnostic significance. The diagnostic value of PR segment changes in determining benign versus malignant pericardial disease in cancer patients with pericardial effusions has not been investigated. We aimed to determine the relationship between PR segment changes and malignant pericardial disease in cancer patients presenting with pericardial effusions. Methods Consecutive patients with active malignancy who underwent surgical subxiphoid pericardial window by a single thoracic surgeon between 2011 and 2014 were included in this study. A total of 104 pre- and post-operative ECGs were reviewed, and PR depression or elevation was defined by deviation of at least 0.5 millivolts from the TP segment using a magnifying glass. Pericardial fluid cytology, flow cytometry and tissue biopsy were evaluated. Baseline characteristics and co-morbidities were compared between cancer patients with benign and malignant pericardial effusions. Results A total of 26 patients with active malignancy and pericardial effusion who underwent pericardial window over the study period were included. Eighteen (69 %) patients had isoelectric PR segments, of whom none (0 %) had evidence of malignant pericardial disease (100 % negative predictive value). Eight (31 %) patients had significant ECG findings (PR segment depression in leads II, III and/or aVF as well as PR elevation in aVR/V1), all 8 (100 %) of whom had pathologically confirmed malignant pericardial disease (100 % positive predictive value). PR segment changes in all 8 patients persisted (up to 11 months) on post-operative serial ECGs. The PR segment changes had no relationship to heart rate or the time of atrial-ventricular conduction. Conclusions In patients with active cancer presenting with pericardial effusion, the presence of PR segment changes is highly predictive of active malignant pericardial disease. When present, PR changes typically persist on serial ECGs even after pericardial window.